Engineering of physicochemical properties and quaternary structure assemblies of avidin and streptavidin, and characterization of avidin related proteins - Laitinen, Olli (2001)
Avidin is a tetrameric glycoprotein found in chicken egg-white. It binds a water soluble vitamin, biotin, with the highest known protein-ligand non-covalent interaction in nature. Streptavidin a protein found in bacteria, is structurally and functionally analogous to avidin. Both avidin and streptavidin are also extremely stable proteins. The avidin gene family, however, has other members: the mysterious avidin-related AVRs genes. However, no one knows if AVRs are expressed at protein level. Our objective was to shed more light on the principles of the oligomerization and stability characteristics of avidin and streptavidin. In addition we wanted to find out, what kind of proteins the as yet unknown AVRs would be. By using the evolutionary approach (i.e. the guidance of structural relatives) we removed the unwanted binding of avidin to certain materials by lowering its pl and by removing its sugar moiety without affecting its biotin-binding and stability characteristics. Using the same approach we also turned tetrameric avidin and streptavidin to dimeric but still biotin-binding forms. The 3-D structure of the avidin was utilized to construct monomeric avidin mutants that when bound to biotin reconstituted tight tetramers. We obtained the first preliminary results for the detailed structural analysis of the studied proteins: the crystallization and X-ray study of the dimeric streptavidin mutant was, unexpectedly, tetrameric in the crystal form. In order to study, whether the proteins encoded by the AVRs were capable of binding biotin and forming tetramers AVR proteins were produced. It was found that all the AVRs bound biotin, although generally with a lower affinity than wild-type avidin. In addition they showed varying physico-chemical properties.